2012
DOI: 10.3389/fnana.2011.00068
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Interhemispheric Connections Develop in Cat Visual Cortex after Early Unilateral Convergent Strabismus: Anatomy, Physiology, and Mechanisms

Abstract: In the mammalian primary visual cortex, the corpus callosum contributes to the unification of the visual hemifields that project to the two hemispheres. Its development depends on visual experience. When this is abnormal, callosal connections must undergo dramatic anatomical and physiological changes. However, data concerning these changes are sparse and incomplete. Thus, little is known about the impact of abnormal postnatal visual experience on the development of callosal connections and their role in unifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 83 publications
0
23
0
1
Order By: Relevance
“…Bilateral connections of the primary visual cortices through the corpus callosum were found to be asymmetrical in cats with induced early unilateral strabismus. Callosal terminals were found to be expanded in the primary visual cortex ipsilateral to the deviated (convergent) eye and almost normal in the contralateral hemisphere (Milleret and Houzel, 2001; Bui Quoc et al, 2012). Using DTI, we recently corroborated these results in humans with infantile strabismus in which we found that visual callosal pathways lack normal pruning (submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral connections of the primary visual cortices through the corpus callosum were found to be asymmetrical in cats with induced early unilateral strabismus. Callosal terminals were found to be expanded in the primary visual cortex ipsilateral to the deviated (convergent) eye and almost normal in the contralateral hemisphere (Milleret and Houzel, 2001; Bui Quoc et al, 2012). Using DTI, we recently corroborated these results in humans with infantile strabismus in which we found that visual callosal pathways lack normal pruning (submitted).…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction (3D) of single callosal axons shows that unilateral convergent strabismus triggers abnormalities in callosal connections (Bui Quoc et al, 2012). Specifically, strabismus induces an extension of interhemispheric terminals into the hemisphere ipsilateral to the deviated eye.…”
Section: Callosal Plasticity: How Visual Input Impacts On Interhemispmentioning
confidence: 99%
“…Unilateral strabismus appeared to cause asymmetrical development of callosal connections (Quoc et al. 2011). This asymmetry possibly precludes the imposition of the central vertical meridian onto the ‘central vertical’, relayed directly from the lateral geniculate nucleus.…”
Section: Could–maldevelopment Of Fusion Pathways Cause Infantile Esotmentioning
confidence: 99%
“…In cats, the callosal visual field subserving fusional convergence subtends twice the angle of the field subserving divergence, similar to the fusional convergence/divergence ratio in humans (Quoc et al. 2011). …”
Section: Introductionmentioning
confidence: 99%